Inovasi Alat Pendeteksi Darah pada Selang Infus untuk Keselamatan Pasien - Suwarmiyati; Amirdan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Infusion therapy is a critical medical procedure widely applied in healthcare facilities, particularly in emergency situations to maintain patients’ fluid balance. However, blood backflow in infusion tubing may cause blockage and increase the risk of clinical complications. This study aims to design and evaluate a blood detection device integrated into an infusion tube to enhance patient safety and support continuous monitoring by healthcare professionals. An experimental method was employed by developing a microcontroller-based system using Arduino Uno, a TCS3200 color sensor for blood detection, and a buzzer as an alert indicator. System testing involved sensor calibration using multiple color variations and simulation of blood backflow conditions in infusion tubing. The results demonstrate that the TCS3200 sensor reliably detects red color as an indicator of blood presence, while other colors such as yellow and pink are not detected. A stable output voltage of 2.2 volts indicates consistent system performance. Overall, the proposed device effectively detects blood-induced blockage in infusion tubing and shows strong potential as a simple early warning system for clinical applications